CONCEPTUAL PRINCIPLES OF AN INTEGRATED CRISIS MANAGEMENT SYSTEM AND ENSURING RESILIENCE IN TRANSFORMATION CONDITIONS - Dmytro Karamyshev; Liudmyla Hordiienko; Valentyn Suvorov (Публічне управління та регіональний розвиток)
Among the problems that need to be solved in the context of the introduction of a national resilience system at both the national and institutional levels are the imperfection of the mechanisms for organizing and coordinating actions in the field of crisis management, interdepartmental interaction in ensuring resilience, ensuring the unity of conceptual and methodological approaches, as well as the principles of functioning of entities ensuring national resilience at different levels. The introduction of an integrated crisis management system will contribute to the realization of opportunities to ensure the resilience of socio-economic systems of different levels on the basis of unified conceptual, organizational and methodological approaches, significantly increase the effectiveness of systemic coordination, timely operational and tactical actions of managers of different levels to prevent and respond to crisis phenomena and dangerous events in conditions of permanent threats and impacts, including hybrid ones. The article substantiates the conceptual principles and organizational and methodological approaches to the formation of an integrated crisis management system and ensuring the resilience of socio-economic systems under transformational conditions. It is noted that the formation of an integrated crisis management system involves the unification of previously isolated parts into a single holistic system, as a result of which the corresponding system has the ability to organize timely and effective crisis management measures at different levels of ensuring the stability of socio-economic systems. It is proven that the formation of an integrated crisis management and stability system requires the development of a comprehensive mechanism for the development and further application of clear organizational and methodological approaches, tactical algorithms, specific tools, effective coordination measures at different levels of functioning and development of socio-economic systems, where the corresponding levels must be interconnected in terms of goals, resources, time, and qualitative characteristics.